„A chłopaki w brecht” — komentarz do Bibliografii przekładów literatury polskiej w Czechach w 2018 roku - Derdowska, Joanna (Przekłady Literatur Słowiańskich, 2020)
The bibliography of Polish literature translated into Czech in 2018 is characterized by a tendency to publish popular and commercially attractive titles: genre fiction and literature for children. The author is concerned with sample passages from Ziemowit Szczerek’s translations of prose published in the A2 literary magazine and discusses possible consequences for the target language of the euphemisation of slang and vulgarisms in the translation of gonzo journalism texts.